Visual Mapping of Program Components to Resources Representation: A 3D Analysis of Grid Parallel Applications - Schnorr, Lucas Mello; Navaux, Philippe Olivier Alexandre; Huard, Guillaume (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2009: Anais do XXI International Symposium on Computer Architecture and High Performance Computing, 2009)
Highly distributed systems such as Grids are usually interconnected by a hierarchical organization of different types of network. This strong network hierarchy influences directly the behavior of parallel applications. In order to obtain a good understanding of parallel application's behavior, the performance analysis must take into account a correspondence between application and network characteristics. This paper presents a novel way to analyze parallel applications, by using a three dimensional visualization and a technique to visually map the application's components to the used resources. This mapping technique is able to handle different types of resources description: different system logical organizations and the description of the network or system interconnection in different levels. The technique, implemented in our prototype Triva, is evaluated through a series of visual representations of the monitoring data obtained through real executions of parallel applications in a grid. The resulting visualizations enable an alternative and powerful way to view and understand various aspects of application behavior together with the network topology.